Awareness, Attitudes, and Perceptions of University Students in Nigeria Toward Contact Lenses for Refractive Error Correction. - Omotor, Oghenevwode Precious; Iyamu, Eghosasere; Okechukwu, Clinton Ifeanyi (Optometry & Visual Performance, 2025)
Background: Contact lenses have become an increasingly popular option for vision correction worldwide, offering both functional and cosmetic advantages. Understanding contact lens usage among university students is crucial for promoting eye health. The goal of the study was to ascertain the knowledge, attitude, and perception of university undergraduates towards contact lenses for refractive error correction. Methods: A survey was used to evaluate the knowledge, attitudes, and perceptions of 377 Life Science students at the University of Benin about using contact lenses for vision correction. The survey was completed both before and after an educational session on contact lenses to measure changes in understanding. Results: The study sample comprised 63.9% females and 36.1% males, with a mean age of 21.83 ± 2.77 years. Only 75 participants (19.9%) had prior experience with contact lenses, of whom 72% used them for cosmetic purposes, while only 28% used them for vision correction. Despite the high awareness of contact lenses (98.1%), specific knowledge about fitting and removal was low (37.4%). Overall, 60.7% of participants had poor knowledge concerning contact lenses for refractive error correction. Attitudes toward contact lenses remained mostly negative before and after the educational session: 64.5% and 60.2%, respectively. Similarly, perceptions of contact lens use stayed negative: 53.3% before education and 54.1% after education. A paired t-test showed that the education did not lead to a significant improvement in attitude (p = 0.130) or perception (p = 0.455). Conclusions: Despite a high level of awareness, misconceptions about contact lenses persist, contributing to low uptake for refractive error correction. Given the limited impact of a single educational intervention, more sustained engagement by eye care practitioners is necessary to address misconceptions and to promote informed decision-making about vision correction options.